YM-155 potentiates the effect of ABT-737 in malignant human glioma cells via survivin and Mcl-1 downregulation in an EGFR-dependent context - Jane, Esther P. (2013)
Antiapoptotic proteins are commonly overexpressed in gliomas, contributing to therapeutic resistance. We recently reported that clinically achievable concentrations of the Bcl-2/Bcl-xL inhibitor ABT-737 failed to induce apoptosis in glioma cells, with persistent expression of survivin and Mcl-1. To address the role of these mediators in glioma apoptosis resistance, we analyzed the effects of YM-155, a survivin suppressant, on survival on a panel of glioma cell lines. YM-155 inhibited growth, and downregulated survivin and Mcl-1 in a dose- and cell line-dependent manner. Whereas U373, LN18, LNZ428, T98G, LN229, and LNZ308 cells exhibited an IC(50) of 10–75 nM, A172 cells were resistant (IC(50) ~ 250 nM). No correlation was found between sensitivity to YM-155 and baseline expression of survivin or cIAP-1/cIAP-2/XIAP. However, strong correlation was observed between EGFR activation levels and YM-155 response, which was confirmed using EGFR-transduced versus wild-type cells. Because we postulated that decreasing Mcl-1 expression may enhance glioma sensitivity to ABT-737, we examined whether cotreatment with YM-155 promoted ABT-737 efficacy. YM-155 synergistically enhanced ABT-737-induced cytotoxicity and caspase-dependent apoptosis. Down-regulation of Mcl-1 using shRNA also enhanced ABT-737-inducing killing, confirming an important role for Mcl-1 in mediating synergism between ABT-737 and YM-155. As with YM-155 alone, sensitivity to YM-155 and ABT-737 inversely correlated with EGFR activation status. However, sensitivity could be restored in highly resistant U87-EGFRvIII cells by inhibition of EGFR or its downstream pathways, highlighting the impact of EGFR signaling on Mcl-1 expression and the relevance of combined targeted therapies to overcome the multiple resistance mechanisms of these aggressive tumors.